Climate security pathway analysis. - Madurga Lopez, Ignacio M.; Dutta Gupta, Tanaya; Liebig, Theresa Ines; Carneiro, Bia; Medina, Leonardo (2023)
The Climate Security Observatory (CSO) is an online platform for stakeholder decision-making that provides access to a range of global analyses related to climate and security. The CSO is based on an integrated climate security framework that helps understand the complexity of the climate-security interface. As part of the CSO methods paper series, this report details the method for analyzing the climate security pathway analysis.